Biomarkers of periodontitis and inflammation in ischemic stroke: A case-control study - Palm, Frederick; Becher, Heiko; Grau, Armin J. (Innate immunity, 2014)
Periodontitis is a common infectious disease associated with increased risk for ischemic stroke though presently unclear mechanisms. In a case-control study, we investigated salivary levels of four periodontal pathogens, as well as systemic and local inflammatory markers. The population comprised 98 patients with acute ischemic stroke (mean ± SD, 68.2 ± 9.7 yrs; 45.9% women) and 100 healthy controls (69.1 ± 5.2 yrs; 47.0% women). Patients were more often edentulous and had fewer teeth than controls (13.8 ± 10.8 versus 16.6 ± 10.1). After adjusting for stroke risk factors and number of teeth, controls had higher saliva matrix metalloproteinase-8 (MMP-8), myeloperoxidase (MPO), IL-1β, Aggregatibacter actinomycetemcomitans, and serum LPS activity levels. Patients had higher serum MMP-8 and MPO, and they were more often qPCR-positive for A. actinomycetemcomitans (37.9% versus 19.0%) and for ≥3 periodontopathic species combined (50.0% versus 33.0%). We conclude that controls more often had evidence of current periodontal infection with higher periodontal pathogen amount, endotoxemia, local inflammation and tissue destruction. Stroke patients more often had evidence of end-stage periodontitis with edentulism and missing teeth. They were more often carriers of several periodontopathic pathogens in saliva, especially A. actinomycetemcomitans. Additionally, inflammatory burden may contribute to high systemic inflammation associated with elevated stroke susceptibility.